(untitled) (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2025)
Listening skills (Maharah Istima’) play an important role in learning Arabic which is often hampered by traditional teaching making students bored and saturated in learning. The purpose of this study was to determine the effectiveness of Arabic language learning using audio-visual media “animation” in Arabic and to improve the listening skills of class VIII students in Arabic language learning at Mts Perguruan mualimat. This study used a quantitative approach with a one-group pretest-posttest experimental design. Data was collected through observation, tests, documentation with a sample of 44 respondents. The results showed a significant increase in the average score of students’ listening skills, from 64.20 in the pretest to 91.32 in the posttest. The hypothesis of this study using a paired sample t test with a significance value of 0.000, identifying a positive effect on the use of audio-visual media on the ability of maharah istima’. The conclusion of this study is that the use of audio-visual media “animation” is proven effective in increasing students’ motivation and understanding in learning Arabic.